KdV on an incoming tide. (30th November 2021) - Laurens, Thierry
Abstract: Given smooth step-like initial data V (0, x ) on the real line, we show that the Korteweg–de Vries equation is globally well-posed for initial data u ( 0, x ) ∈ V ( 0, x ) + H − 1 ( R ) . The proof uses our general well-posedness result (2021 arXiv:2104.11346 ). As a prerequisite, we show that KdV is globally well-posed for H 3 ( R ) perturbations of step-like initial data. In the case V ≡ 0, we obtain a new proof of the Bona–Smith theorem (Bona and Smith 1975 Trans. R. Soc. A 278 555–601) using the low-regularity methods that established the sharp well-posedness of KdV in H −1 (Killip and Vişan 2019 Ann. Math. 190 249–305).